Data mining process for fraud detection in mobile communication - Jelena Mamčenko; Regina Kulvietienė (Lietuvos Matematikos Rinkinys)
Without dependence from a sort of activity (sale, rendering of services, etc.) the using of data mining methods can bring the certain advantage. Fraud detection methods of data mining can be applied to this problem quite readily. Three important elements of a data mining application/solution are present. These are the ability to handle large amounts of data, suitable methods and algorithms, and the availability of domain expertise.